2023
DOI: 10.3390/fishes8050235
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Pathogenic Vibrio Species in Black Rockfish Sebastes schlegeli

Abstract: Four pathogenic Vibrio species were isolated from three diseased black rockfish Sebastes schlegeli in Yantai, Shandong Province, China. The strains were identified based on physiological and biochemical characteristics and 16S rDNA sequencing and named SF-2, SF-3, SF-5, and SF-6, respectively. SF-2 was Vibrio scophthalmi, SF-3 was V. harveyi, SF-5 was V. alginolyticus, and SF-6 was V. parahaemolyticus. This is the first time that V. scophthalmi was isolated from black rockfish. The present research shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Analysis of 16S rRNA sequences from Vibrio species isolated from aquaculture waters showed that V. harveyi (25%), V. anguillarum (12.5%), and V. scophthalmi (12.5%) had higher rates compared to other Vibrio species. These species are already frequently isolated during vibriosis outbreaks [49,50]. Vibrio harveyi is frequently found in shrimp cultures, whereas Vibrio anguillarum is commonly associated with disease in sea bass and trout [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 16S rRNA sequences from Vibrio species isolated from aquaculture waters showed that V. harveyi (25%), V. anguillarum (12.5%), and V. scophthalmi (12.5%) had higher rates compared to other Vibrio species. These species are already frequently isolated during vibriosis outbreaks [49,50]. Vibrio harveyi is frequently found in shrimp cultures, whereas Vibrio anguillarum is commonly associated with disease in sea bass and trout [51][52][53].…”
Section: Discussionmentioning
confidence: 99%